POLA KEPEMIMPINAN CAMAT DALAM MENJALANKANADMINISTRATIF PADA KECAMATAN MINAS KABUPATEN SIAK LEADERSHIP PATTERNS DISTRICT IN IMPLEMENTING ADMINISTRATION IN MINAS DISTRICT, SIAK REGENCY - Nielwaty, Elly; Fara Merian Sari; Nurmala Boru Siregar; Dwi Herlinda; Afni.Z (Cahaya Ilmu Bangsa, 2024)
Abstract This research discusses the leadership pattern of sub-district heads in carrying out administrative functions in Minas District, Siak Regency. Leadership patterns are the way a leader guides, directs and motivates members of his team or organization. The phenomenon found in this research is that there is still a lack of communication coordination between sub-district leaders and the community and timely decision making is still not optimal. The aim of this research is to determine the leadership pattern of the sub-district head in Minas District, Siak Regency and to determine the obstacles faced by the sub-district leadership in carrying out administrative functions in Minas District, Siak Regency. The theory used in this research is the theory of Martoyo, S (2015: 497), the leadership patterns used are divided into six, namely, analytical and decision making abilities, motivational abilities and skills, communication and listening abilities, the ability to create a healthy work environment, the ability to delegate duties or authority, and responsibilities. This research uses qualitative methods, data collection uses interview techniques, direct observation and documentation. The results of this research are that the lack of coordination between sub- district leaders and the community is still not optimal, which causes the sub-district leadership's conveyance of aims and objectives to not be understood and in carrying out administrative functions, the connection factor is an obstacle for leaders in situations requiring leaders to make decisions. Keywords : Leadership, Leadership Pattern, Administratife Functions.